Next-generation water-saving strategies for greenhouses using a nexus approach with modern technologies - Hao Zou; Fan Wang; Ziya Zeng; Jingling Zhu; Linyan Zha; Danfeng Huang; Jun Li; Ruzhu Wang (Nature Communications, 2025)
Abstract The escalating food and water crisis, propelled by population growth, urbanization, and climate change, demands a reimagining of agricultural practices. Traditional water-saving irrigation methods have reached their limits, necessitating the exploration of innovative approaches. This perspective explores the potential of utilizing excess light and water in greenhouse cultivation through advanced materials and engineering technologies. We investigate the potential of four key technologies—sorption-based atmosphere water harvesting (SAWH), superabsorbent polymer water holding materials (SPWH), radiative cooling (RC), and seawater desalination. The perspective proposes suitable application methods and future development directions for greenhouse water conservation, aiming to introduce novel water-saving strategies and smarter resource management.